Women and Work in Preindustrial Europe - Hanawalt, Barbara (Indiana University Press, 1986)
The working women in this volume represent a wide diversity of stations in life, ranging from slaves and servants to respectable widows and professional midwives. Through a variety of sources including notarial records, wills, contracts, private account books, and city, manorial, and state court records, their work patterns come to life. The women studied lived in Page viii →Ragusa (Dubrovnik), Florence, Lyon and Montpellier, Exeter and rural England, Cologne, Leiden, and Nuremberg. With such a variety of work experiences, locations, and centuries separating their lives, a remarkable continuity of circumstances and options nevertheless emerges.